The emerging role of tacrolimus in myasthenia gravis. (March 2015) - Cruz, Jennifer L.; Wolff, Marissa L.; Vanderman, Adam J.; Brown, Jamie N.
Objective: To describe and evaluate the available evidence assessing the role of tacrolimus in the management of patients with myasthenia gravis (MG). Data sources: A literature search of MEDLINE (1946 to September 2014) and EMBASE (1947 to September 2014) was performed using the terms 'tacrolimus' and 'myasthenia gravis'. Citations of retrieved articles were examined for relevance. Study selection and data extraction: The search was limited to prospective clinical trials focused on clinical outcomes in patients with generalized MG. Case reports, retrospective evaluations and non-English articles were excluded. Data synthesis: A total of 12 studies met inclusion criteria, of which seven articles evaluated tacrolimus in steroid-dependent patients and two examined the utility of tacrolimus in patients failing corticosteroids and cyclosporine. Other studies evaluated early initiation of tacrolimus after thymectomy, effectiveness of tacrolimus in de novo MG and the effectiveness of tacrolimus post-thymectomy in thymoma patients versus nonthymoma. A total of eight trials showed statistically significant improvements in quantitative MG score (QMGS) and postintervention status criteria – Myasthenia Gravis Foundation of America (PSC-MGFA). Of the trials examining steroid reduction with tacrolimus, two reported high rates of complete withdrawal; however, the most robust trial was unable to detect a difference in mean steroid dose. Long-term effects of tacrolimus (up to 5 years) were assessed in eight trials, which consistently showed positive effects on QMGS or reduction in adjunct therapies. Conclusions: There is limited yet promising information to suggest a beneficial role for tacrolimus in reducing QMGS and corticosteroid burden in patients with refractory symptoms or new-onset MG. Long-term use appears to be safe in this population.